Altered Toll-Like Receptor-4 Response to Lipopolysaccharides in Infants Exposed to HIV-1 and Its Preventive Therapy - Maloupazoa Siawaya, Anicet Christel; Mvoundza Ndjindji, Ofilia; Kuissi Kamgaing, Eliane; Mveang-Nzoghe, Amandine; Mbani Mpega, Chérone Nancy; Leboueny, Marielle; Kengue Boussougou, Roselyne; Mintsa Ndong, Armel; Essone, Paulin N.; Djoba Siawaya, Joel Fleury (Frontiers in Immunology, 2018)
Pathogen sensing and recognition through pattern recognition receptors, and subsequent production of proinflammatory cytokines, is the cornerstone of the innate immune system. Despite the fact that HIV exposed uninfected (HEU) infants are prone to serious bacterial infections, no study has focused on the functionality of their bacteria recognition system. This is the first study to investigate baseline levels of three critically important immune response molecules in this population: Complement component (C)-3, toll like receptor (TLR)-4 and C-reactive protein (CRP). We enrolled 16 HEU- and 6 HIV unexposed (HU)-infants. TLR4 function was investigated by stimulating whole blood with increasing concentrations of TLR4-agonist Ultrapure lipopolysaccharides (LPS). Complement C3 and CRP were measured by photo spectrometry. Data showed no significant differences in baseline concentration of CRP between HEU- and HU-infants. Complement C3 was significantly higher in HEU-infants than HU-infants. TLR4 anergy was observed in 7 out of 12 HEU-infants, whereas the rest of HEU (n = 4) and the control HU-infants tested (n=3) showed responsive TLR4. None of the HEU-infants investigated in this study had severe infections in the year after their birth. In conclusion, TLR4 anergy can occur in HEU-infants without necessarily translating to increased vulnerability to infectious diseases.